End-User Preferences for Spreader Layout - Shahadan, Saad (2011)
Acquiring information about user preferences for forum chat layout can be the key for continuously access of the portal. Forum chat is a chatting technique that commonly uses in social networking website. Using forum chat all users can post their stories in front of body layout of website then other users can comment it. Computer Science Department of UiTM Kedah needs to develop a portal that can give interactive session between Computer Science’s Lecturers and their students. From the set of possible behaviour, two different layouts will propose for developing prototype of Computer Science Department Portal which includes online forum chat spot name as Spreader. This research proposed an importance measure that considers which layout most prefer by end-users base on Nielsen's criteria; learnability and user satisfaction. With this information, a new analysis to place Spreader in portal layout successfully performed. This analysis can acts as guideline for applying in any other portal in order to make portal become more interactive than before. The respective results give very important insight regarding end-user preferences and prompt the interactivity of the portal layout.